Alterations of starch structure lead to increased resistant starch of steamed rice: Identification of high resistant starch rice lines. (March 2016) - Tsuiki, Kaori; Fujisawa, Haruka; Itoh, Ayaka; Sato, Masao; Fujita, Naoko
Abstract: The development of low calorie foods to aid obesity control is a growing area of research. Among these, resistant starch (RS) in cereals has beneficial effects on reducing colon cancer rate and better fatty acid composition as well as lowering calories. Rice contains digestible starch and indigestible RS, the proportions of which are affected by starch biosynthetic enzymes. Rice lines that carry mutations in starch biosynthesis genes may have high levels of RS. In this study, percentage RS and non-digested component values were determined in steamed rice from several rice lines. These include several high-amylose indica rice cultivars, and lines carrying mutations in the starch synthase (SS) IIIa and/or branching enzyme (BE) IIb genes. High RS rice lines contained high levels of non-digested component. RS values ≤ 4% correlated with apparent amylose content. RS values of BEIIb-deficient mutant lines were particularly high (15 ≤ RS ≤ 35%), and were correlated with the amount of amylopectin long chains. Among rice lines used in this study, be2b mutant lines having large portions of amylopectin long chains were the best candidates for high RS rice foods. Highlights: High amylose rice lines have high resistant starch (RS) content in the steamed rice. High RS rice lines contained high levels of non-digested component. RS values of branching enzymes IIb-deficient mutant lines were particularly high. RS values were correlated with the amount of amylopectin long chains.